DAMPAK DARI LINGKUNGAN KERJA DAN DUKUNGAN ORGANISASI TERHADAP MOTIVASI KERJA KARYAWAN PADA PT MARUWA BATAM - Ludiya, Hielvita (Jurnal Terapan Manajemen dan Bisnis, 2017)
The majority of organizations are competing to survive in this volatile and fierce market Environment. Organizations that can successfully retain their human resources have an advantage over organizations that cannot. The study tested âThe Influence of Work Environment and Organizational Support on Employee Motivation at PT Maruwa in Batam Cityâ. The questionnaire distributed to 140 employee at One Factory, particular in B Shift but received 130 questionnaires. The sampling method in this research done with the approach of non-probability sampling with the simple purposive sampling. Scale of measurement used Likert items is five-point scale. Scale of measurement used Likert items a five-point scale range from strongly disagree on one until strongly agree. The collected data was analyzed using SPSS version 11.5 for Windows. The findings showed that work environmental has a significant positive effect on employee motivation, and organizational support has a significant positive effect on employee motivation. The limitations and implications and the study also discussed.